Coping Strategies of Female-Headed Households in Urban Poor Communities in the Philippines - Torres, Amaryllis T. (Review of Women's Studies; Vol 4 No 1 (1994): Review of Women's Studies Volume IV, Number 1 (1993-1994))
---